Animasi Propagule Journey dalam Meningkatkan Pemahaman Pelestarian Mangrove - Selly Artaty Zega; Aldian Husein; Maria (Politeknik Negeri Batam, 2026)
Indonesia has the most extensive mangrove ecosystem in the world, but its condition is worsening due to a lack of environmental awareness and outdated teaching approaches. This research intends to create the Propagul Journey educational animation using the 4D model, which includes Define, Design, Develop, and Disseminate phases. During the Define stage, a knowledge gap was recognized and tackled using a